Response of Rice Hybrids to Nitrogen Levels under Lateritic Zone of West Bengal, India - Bera, A. K.; Pramanik, K. (International Journal of Bio-resource and Stress Management, 2023)
A pot culture experiment was conducted during kharif season of 2009 and 2010 at Agricultural research farm, Visva-Bharati, Sriniketan, Birbhum. The experiment was laid out in CRD with three rice hybrids, viz. PHB-71, 25P25 and KRH-2, and four levels of nitrogen, viz. N0, N50, N100 and N150 kg ha-1. Among hybrids, PHB-71 produced significantly higher total chlorophyll content, panicle length, panicle weight, filled grains panicle-1, grain yield hill-1 and harvest index as compared to 25P25 and KRH-2 during both years. PHB-71 produced significantly highest grain yield of 43.38 and 46.23 g hill-1 in 2009 and 2010, respectively, which showed an increase of 42.08 and 45.23% over rice hybrid 25P25 and KRH-2, respectively. The two years pooled of grain yield hill-1 of rice hybrid PHB-71 was significantly higher as compared to others. Variation in nitrogen dose had marked effect on all the yield attributing traits. Application of N @ 150 kg ha-1 significantly increased total chlorophyll content, yield contributing parameters and yield as compared with 0, 50, 100 kg N ha-1. Application of 150 kg N ha-1 recorded significantly higher grain yield hill-1 as compared to lower nitrogen levels. The pooled grain yield of PHB-71 was significantly higher as compared to 25P25 and KRH-2.